Influence of temperature and pH on the anammox process: A review and meta-analysis. (September 2017) - Tomaszewski, Mariusz; Cema, Grzegorz; Ziembińska-Buczyńska, Aleksandra
Abstract: The anammox (anaerobic ammonium oxidation) process was considered a very efficient and economic wastewater treatment technology immediately after its discovery in 1995, thus research in this field was intensified. The anammox process is characterised by a high temperature optimum and is very sensitive to both temperature and pH fluctuations. The process can also be inhibited by many factors, including by its substrates, i.e. nitrite and ammonium (or its unionised forms: free ammonia and free nitrous acid). This paper presents a comprehensive study of the most important and recent findings on the influence of two parameters that are crucial in wastewater treatment, i.e. temperature and pH. Because both parameters may influence the anammox process simultaneously, a meta-analysis was conducted of the data from the literature. Although meta-analysis is commonly used in medical research, mathematical analysis of the literature data has become an interesting and important step in the environmental sciences. This paper presents information on the influence of both temperature and pH on process efficiency and microbial composition. Additionally, the responses of different operating systems on both temperature and pH changes are described. Moreover, the role of both adaptation to changed conditions and of pH control as well as indicated areas of process operation are discussed. Highlights: Individual and simultaneous influence of temperature and pH were reviewed. Mathematical analysis of the literature data was conducted. Reaction kinetics changes at low temperatures. B. sinica and K. stuttgartiensis - species able to adapt to low temperatures. Meta-analysis suggests the greater importance of pH at lower temperatures.